2019
DOI: 10.1039/c8ta10142f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically activated cobalt nickel sulfide for an efficient oxygen evolution reaction: partial amorphization and phase control

Abstract: It has recently been demonstrated that the OER activity of transition metal sulfides (TMSs) could be enhanced by the introduction of a thin amorphous layer on a pristine surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…[ 9,10 ] Transition metal compounds, specifically, those containing Co, Ni, or Fe along with non‐metals such as O, N, S, Se, and P, are promising OER catalysts capable of outperforming benchmark IrO 2 and RuO 2 catalysts in alkaline solution. [ 11–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 9,10 ] Transition metal compounds, specifically, those containing Co, Ni, or Fe along with non‐metals such as O, N, S, Se, and P, are promising OER catalysts capable of outperforming benchmark IrO 2 and RuO 2 catalysts in alkaline solution. [ 11–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Kolyagin and Kornienko, who investigated the wetting of porous hydrophobized gas diffusion electrodes, calculated the double‐layer capacitance related to the total surface area wetted by electrolyte from the slopes of the tangents to the data obtained at low scan‐rates leaving out the higher potential scan‐rates where the plot deviates from linear behaviour [92] . Other authors, in turn, simply assume a linear relationship and calculate the double‐layer capacitance from the line of best fit [93–95] . However, the authors ascribed deviation of specific capacitance from linearity with increasing potential scan‐rate to be due to i) an easily accessible outer surface area, C outer , that can be readily charged particularly at high potential scan‐rates and ii) an inner surface area, C inner , created by the pore network within the catalyst particle structure, which is less accessible due to mass transfer/diffusion limitation of ions resulting in less charge stored and lower double‐layer capacitance values, respectively [90,91,96] .…”
Section: Resultsmentioning
confidence: 99%
“…[92] Other authors, in turn, simply assume a linear relationship and calculate the double-layer capacitance from the line of best fit. [93][94][95] However, the authors ascribed deviation of specific capacitance from linearity with increasing potential scan-rate to be due to i) an easily accessible outer surface area, C outer , that can be readily charged particularly at high potential scan-rates and ii) an inner surface area, C inner , created by the pore network within the catalyst particle structure, which is less accessible due to mass transfer/diffusion limitation of ions resulting in less charge stored and lower double-layer capacitance values, respectively. [90,91,96] Therefore, capacitance at low potential scan-rates is representative of the total surface capacitance, i. e., the capacitance due to inner and outer surface area, whereas the capacitance at higher potential scan-rates corresponds to the charge of easily accessible outer surface area.…”
Section: Orr Activity and Stability Evaluationmentioning
confidence: 99%
“…The resulting phase boundaries will significantly harmonize the respective advantages of amorphous and crystalline phases. However, the study of such catalysts has rarely been reported . Iron is relatively biocompatible and often serves as a central element in biological systems .…”
Section: Figurementioning
confidence: 99%